Fracture hydromechanical response measured by fiber optic distributed acoustic sensing at milliHertz frequencies. Issue 14 (25th July 2017) - Becker, M. W.; Ciervo, C.; Cole, M.; Coleman, T.; Mondanos, M.
Abstract: A new method of measuring dynamic strain in boreholes was used to record fracture displacement in response to head oscillation. Fiber optic distributed acoustic sensing (DAS) was used to measure strain at mHz frequencies, rather than the Hz to kHz frequencies typical for seismic and acoustic monitoring. Fiber optic cable was mechanically coupled to the wall of a borehole drilled into fractured crystalline bedrock. Oscillating hydraulic signals were applied at a companion borehole 30 m away. The DAS instrument measured fracture displacement at frequencies of less than 1 mHz and amplitudes of less than 1 nm, in response to fluid pressure changes of less 20 Pa (2 mm H2 O). Displacement was linearly related to the log of effective stress, a relationship typically explained by the effect of self‐affine fracture roughness on fracture closure. These results imply that fracture roughness affects closure even when displacement is a million times smaller than the fracture aperture. Key Points: Nanometer fracture displacement was measured in response to millimeter head oscillation in a fractured crystalline bedrock Fracture stress strain was semilogarithmic at displacements a million times smaller than the aperture Measured stress‐strain relationship suggests self‐affine fracture roughness controls closure at nanometer scales Plain Language Summary: The behavior of rock formations when stressed by fluid injection or pumping is important for hydrofracturing of petroleum reservoirs, development and operation of geothermal reservoirs, and monitoring of geologic sequestration of carbon dioxide among other operations. We demonstrate a new application of a recent but commercially available technology called Distributed Acoustic Sensing (DAS) which is mainly used to listen to well flow or sense seismic response. DAS senses oscillating strain along a fiber optic cable to measure vibration at thousands of points in the subsurface. Our innovation is to sense similar responses at much lower frequencies, so the response to pumping and injection can be measured. Fracture opening and closing of less than a nanometer was sensed in response to pressure oscillations of less than 2 mm of water level. Because fiber optic cable can be installed in harsh environments for long periods of time, the technology holds promise for environmental monitoring of sensitive geologic operations. Fracture closure a million times smaller than the fracture aperture appeared to be controlled by the roughness of the fractures, based upon similar studies performed for much larger closures.